Effects of Interest Rate, Exchange Rate and their Volatilities on Stock Price of Nepalese Commercial Banks - Shrestha, Manoj (Nepalese Journal of Economics, 2024)
This study examines the effects of interest rate, exchange rate and their volatilities on stock price of Nepalese commercial banks. Stock price and stock return are the selected dependent variables. The selected independent variables are bank rate, deposit interest rate, lending interest rate, base rate, volatility of interest rate and exchange rate. The study is based on secondary data of 14 commercial banks with 140 observations for the study period from 2013/14 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, reports published by Ministry of Finance and annual report of respective commercial banks and NEPSE. The correlation coefficients and regression models are estimated to test the significance and importance of bank rate, deposit interest rate, lending interest rate, base rate, volatility of interest rate and exchange rate on stock price of Nepalese commercial banks. The result showed that bank rate has a positive effect on stock price and stock return. It means that increase in bank rate leads to increase in stock price and stock return. Likewise, deposit interest rate has a negative effect on stock price and stock return. It means that increase in deposit interest rate leads to decrease in stock price and stock return. Similarly, lending interest rate has a negative impact on stock price and stock return. It shows that higher the lending interest rate, lower would be the stock price and stock return. Additionally, base rate has a negative effect on stock price and stock return. It indicates that increase in base rate leads to decrease in stock price and stock return. However, volatility of interest rate has a negative effect on stock price and stock return. It indicates that increase in volatility of interest rate leads to decrease in stock price and stock return. Further, this study showed that exchange rate has a negative effect on stock price and stock return. It means that higher the exchange rate, lower would be the stock price and stock return.